Multi-layered proteogenomic analysis unravels cancer metastasis directed by MMP-2 and focal adhesion kinase signaling - Yumi Kwon (Nature Portfolio, 2021)
Abstract The role of matrix metalloproteinase-2 (MMP-2) in tumor cell migration has been widely studied, however, the characteristics and effects of MMP-2 in clinical sample of metastatic colorectal cancer (CRC) remain poorly understood. Here, in order to unveil the perturbed proteomic signal during MMP-2 induced cancer progression, we analyzed plasma proteome of CRC patients according to disease progression, HCT116 cancer secretome upon MMP-2 knockdown, and publicly available CRC tissue proteome data. Collectively, the integrative analysis of multi-layered proteomes revealed that a protein cluster containing EMT (Epithelial-to-Mesenchymal Transition)-associated proteins such as CD9-integrin as well as MMP-2. The proteins of the cluster were regulated by MMP-2 perturbation and exhibited significantly increased expressions in tissue and plasma as disease progressed from TNM (Tumor, Node, and Metastasis) stage I to II. Furthermore, we also identified a plausible association between MMP-2 up-regulation and activation of focal adhesion kinase signaling in the proteogenomic analysis of CRC patient tissues. Based on these comparative and integrative analyses, we suggest that the high invasiveness in the metastatic CRC resulted from increased secretion of MMP-2 and CD9-integrin complex mediated by FAK signaling activation.